Albendazole-cyclodextrins binary systems Thermal and spectral investigation on drug-excipient interaction - Trandafirescu Cristina; Ledeţi Ionuţ; Soica Codruta; Ledeti Adriana; Vlase Gabriela; Borcan Florin; Dehelean Cristina; Coricovac Dorina; Racoviceanu Roxana Marcela; Aigner Zoltán (2019)
The aim of this study was to characterize the interaction between the binary systems of albendazole (ABZ)-cyclodextrins (CDs) with pharmaceutical excipients. Hydroxyl-propyl-beta-cyclodextrin (HPBCD) and random methyl-beta-cyclodextrin (RAMEB) were used as cyclodextrins and magnesium stearate, mannitol, polyvinylpyrrolidone K30 (PVP K30), colloidal silica, starch, and talc were used as excipients. The utilized investigation techniques were attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), powder X-ray diffractometry (PXRD) and thermoanalytical techniques: thermogravimetry (TG)/derivative thermogravimetry (DTG)/heat flow (HF) and differential scanning calorimetry (DSC). The ATR-FTIR analysis clearly suggested interactions under ambient conditions between ABZ-HPBCD with PVP K30 and SiO2 and between ABZ-RAMEB with SiO2 and talc. The PXRD patterns indicated the formation of less crystalline mixtures but with no clear indication of interactions, since no peaks appeared nor disappeared. The modifications on the DSC curves suggested an interaction between ABZ-HPBCD and PVP K30 and SiO2 respectively, and in case of ABZ-RAMEB was observed an interaction with talc. Thermal analysis (TG/DTG/HF) carried out in open crucibles in dynamic air atmosphere suggested that at temperatures over 40 degrees C dehydration of samples occurred, later followed by thermolysis and appearance of interactions in all studied cases. Our study concludes by recommending precautionary measures in elaborating new solid formulations containing ABZ, HPBCD and PVP K30/SiO2 and for the ones containing ABZ, RAMEB and Talc/SiO2, due to the present interactions under ambient conditions.